2020
DOI: 10.3390/en13215570
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Assessment of the Potential of Low Percentage Green Hydrogen Blending in the Italian Natural Gas Network

Abstract: The growing rate of electricity generation from renewables is leading to new operational and management issues on the power grid because the electricity generated exceeds local requirements and the transportation or storage capacities are inadequate. An interesting option that is under investigation by several years is the opportunity to use the renewable electricity surplus to power electrolyzers that split water into its component parts, with the hydrogen being directly injected into natural gas pipelines fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…A potential option to gradually upscale hydrogen pathways is the integration in existing natural gas networks. This is being proposed in different European countries [32][33][34] to exploit existing assets and start to decrease the carbon intensity of natural gas by using clean hydrogen. However, such strategy has the strong limitation of not fully exploiting the higher value associated with pure hydrogen, by mixing it with natural gas to be used in combustion processes.…”
Section: Hydrogen Blending In Natural Gas Gridsmentioning
confidence: 99%
“…A potential option to gradually upscale hydrogen pathways is the integration in existing natural gas networks. This is being proposed in different European countries [32][33][34] to exploit existing assets and start to decrease the carbon intensity of natural gas by using clean hydrogen. However, such strategy has the strong limitation of not fully exploiting the higher value associated with pure hydrogen, by mixing it with natural gas to be used in combustion processes.…”
Section: Hydrogen Blending In Natural Gas Gridsmentioning
confidence: 99%
“…Preliminary assessments and tests in the EU countries [3], [5]- [7] show that it is urgent to evaluate at the same time (i) the potential of green hydrogen blending at low percentage (up to 10%) and (ii) the maximum of available P2H capacity compatible with low percentage blending. If the first estimates purely theoretically calculate the maximum possible amounts of hydrogen gas that can be filled into the existing national NG networks at low impurity concentrations [5], [6], then real experiments are performed in separate network sections, e.g., in Germany and Denmark with "windgas", France (Dunkerque), the UK (Keele, Leeds), Italy (Salerno).…”
Section: The Main Aspects From Experience Of Other Eu Countriesmentioning
confidence: 99%
“…In Italy, two different networks are operated [6]: the transportation and the distribution networks. More than 90 % of natu-ral gas is imported from foreign countries through 7 points.…”
Section: The Main Aspects From Experience Of Other Eu Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an investigation of the impact of hydrogen in power-to-gas networks where the entire system was analysed from a material aspect standpoint, Gondal states that only a 2% of H 2 by volume can be blended in the networks with negligible effects, particularly due to the impacts on specific end applications such as gas turbines and engines [17]. Recently, Pellegrini et al, in a study assessing the potential of green hydrogen blending in the Italian natural gas network, concluded that grid adaptations in critical components and adjustments to the end-user will be necessary to deliver the ambitious goals of the European hydrogen strategy [18].…”
Section: Introductionmentioning
confidence: 99%